AFT Pattimura CSR Pentahelix Collaboration in the Implementation of Waste Management Center Social Innovation Program: NEKAT SA (Negeri Katong Tanpa Sampah) - Tiara Chaerani; Samuel F. Sayaranamual; Ken Bima Prawira Atmaja; Sara Marlis Youwe (Jurnal Indonesia Sosial Teknologi, 2024)
The Waste Management Center: NEKAT SA (Negeri Katong Tanpa Sampah) program, initiated by PT Pertamina Patra Niaga Aviation Fuel Terminal Pattimura, represents a social innovation aimed at addressing waste management issues in Negeri Laha through a pentahelix collaboration approach. This approach entails the cooperation of five key elements: businesses, government, academia, media, and the community. The program integrates four community empowerment initiatives through CSR AFT Pattimura partners, functioning as community groups that implement waste management programs across three primary stages: upstream (education and waste collection), process (converting waste into valuable products), and downstream (establishing a circular economy). The program emphasizes zero waste and circular economy principles by managing organic, inorganic, and residual waste into valuable products that can enhance the income of beneficiary communities. This study employs a descriptive analytical method to delineate the roles of each stakeholder in the implementation of the NEKAT SA program. Primary data were gathered from field implementation processes, while secondary data were sourced from literature reviews and documentation. The findings indicate that the pentahelix collaboration approach in the NEKAT SA program is effective in mitigating waste issues, increasing community income, and fostering a culture of cleanliness and health. The success of this program underscores the importance of sustained commitment from all involved stakeholders to ensure the ongoing positive environmental and economic impacts in Negeri Laha.